2005
DOI: 10.1083/jcb.200504124
|View full text |Cite
|
Sign up to set email alerts
|

FAK signaling is critical for ErbB-2/ErbB-3 receptor cooperation for oncogenic transformation and invasion

Abstract: The overexpression of members of the ErbB tyrosine kinase receptor family has been associated with cancer progression. We demonstrate that focal adhesion kinase (FAK) is essential for oncogenic transformation and cell invasion that is induced by ErbB-2 and -3 receptor signaling. ErbB-2/3 overexpression in FAK-deficient cells fails to promote cell transformation and rescue chemotaxis deficiency. Restoration of FAK rescues both oncogenic transformation and invasion that is induced by ErbB-2/3 in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
134
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(145 citation statements)
references
References 41 publications
7
134
1
2
Order By: Relevance
“…This conclusion is supported by the fact that v-Src-stimulated cell invasion is linked to the formation of a FAK-Src-p130Cas-Dock180 signaling complex, elevated Rac and JNK activation and increased MMP expression and activity (Hsia et al, 2003). Further, inhibition of Src and MAPK activation blocks an ErbB2/3 to FAK signaling linkage, promoting cell invasion (Benlimame et al, 2005). As we found that uPA expression in 4T1 FAK shRNA cells was rescued by constitutively active MEK1 or WT JNK1 expression, it is likely that multiple signaling pathways downstream of FAK contribute to uPA expression, cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This conclusion is supported by the fact that v-Src-stimulated cell invasion is linked to the formation of a FAK-Src-p130Cas-Dock180 signaling complex, elevated Rac and JNK activation and increased MMP expression and activity (Hsia et al, 2003). Further, inhibition of Src and MAPK activation blocks an ErbB2/3 to FAK signaling linkage, promoting cell invasion (Benlimame et al, 2005). As we found that uPA expression in 4T1 FAK shRNA cells was rescued by constitutively active MEK1 or WT JNK1 expression, it is likely that multiple signaling pathways downstream of FAK contribute to uPA expression, cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 92%
“…Owing to these concerns, recent studies have used RNAi to reduce FAK expression. In human MDA-231 breast carcinoma cells, anti-FAK RNAi resulted in the inhibition of lung metastasis after orthotopic implantation in nude mice (Benlimame et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, aberrant trafficking of integrins to the leading edge has been documented to activate the matrix-degrading proteases such as matrix metalloproteinases (MMPs) and plasmin, required for degradation of the ECM and subsequent cell invasion [38,40]. Moreover, stimulation of cells with the growth factor heregulin (HRG), has been shown to affect the expression and serine phosphorylation status of the focal adhesion protein paxillin, resulting in both the induction of morphological changes in cell shape as well as the stimulation of cell scattering in the breast cancer epithelial cell line, MCF-7 [41][42][43]. Paxillin has also been implicated in contributing to tumor invasiveness and metastasis in breast cancer, non-small cell lung cancer, prostate cancer and osteosarcomas [41][42][43].…”
Section: Moving Toward Metastasismentioning
confidence: 99%
“…Moreover, stimulation of cells with the growth factor heregulin (HRG), has been shown to affect the expression and serine phosphorylation status of the focal adhesion protein paxillin, resulting in both the induction of morphological changes in cell shape as well as the stimulation of cell scattering in the breast cancer epithelial cell line, MCF-7 [41][42][43]. Paxillin has also been implicated in contributing to tumor invasiveness and metastasis in breast cancer, non-small cell lung cancer, prostate cancer and osteosarcomas [41][42][43]. Lastly, over-expression of FAK has been documented in invasive and metastatic breast, colon, thyroid and prostate cancers [44,45].…”
Section: Moving Toward Metastasismentioning
confidence: 99%
See 1 more Smart Citation